Connecting NEET (in)to local social institutions through IPB and ADRAT - Gonçalves, Vitor (2021)
In the last months, the unemployment rate of the active population aged between 15 and 74 years old increase drastically in all countries due the COVID-19. The needs to reintegrate young people in the labor market are even more big challenges. Since we have Meeting Points for NEETs (not in education, employment, or training) opened in the context of this project (SOCIAL NEET), we can use each meeting point to inform NEETs about training courses in Education for Entrepreneurship. So, we are planning a training course to facilitate to the NEETs the acquisition of skills and competences to create ideas of projects more creative, innovative, distinctive and sustainable and, consequently, an entrepreneurial spirit based on those competencies to elaborate a different project or business plan. Firstly, we will clarify the training methodologies to promote a training or a career plan. After acquiring the essential entrepreneurship skills and tools for generating and describing a business model or project, the NEETs will be challenged to generate business or project ideas, particularly in the social area. Generally speaking, first, the workgroups will use the Design Thinking and the Disney’s Creative Strategy in order to explore their business idea from a number of complementary points of view, e.g. according to three of Disney’s different roles: the Dreamer, the Designer, and the Critic. Then they will use the Business Model Canvas proposed by Alexander Osterwalder to present the business idea. Finally, they will describe the business plans, filling out the corresponding models proposed by the Agency for Competitiveness and Innovation. This communication presents the planning process of a social micro-business or a project, thus contributing to the promotion of education for social entrepreneurship and consequently to the improvement of employability issues and trends.